Political Communication Strategy of The Yogyakarta Sultanate in The Reform Era: Media, Religion and Cultural Approaches - Slamet Slamet (Eduvest - Journal of Universal Studies, 2025)
This study aims to analyze the political communication strategy carried out by the Sultanate of Yogyakarta in the reform era which included the political communication of the Yogyakarta Sultanate through media, religious and cultural approaches. These three approaches cannot be separated from the position of Sultan Hamengkubuwono who is a government political leader as well as a cultural leader and religious leader. The findings of this study state that the Sultanate of Yogyakarta has a political communication strategy that includes media, religious and cultural approaches. In terms of the media approach, the Yogyakarta Sultanate was carried out through mass media, namely the word rubric in Kedaulatan Rakyat. Also through book publications that contain the Sultan's political ideas. As for the religious approach, the Sultanate of Yogyakarta uses Pathok Negoro Mosque and Grebeg Ceremony as a medium for political communication. In the cultural approach, it uses the tradition of Pisowanan Ageng, Cermo, Wayang Kulit, and the Titah Raja for its political communication media. This study also strengthens the statement that the success of decentralization of democracy in Indonesia cannot be separated from the socio-cultural conditions that lie behind it.